1999
DOI: 10.1557/proc-556-1215
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Properties of Heavy Liquid Metal Targets of Accelerator Driven Systems

Abstract: The long-lived radioactivity of lead-bismuth coolant (LBC) inside the targets of the accelerator driven systems (ADS) is estimated. It is determined by both spallation and fission products of lead and bismuth nuclides. Based on US safety standards the radiotoxicity of targets was calculated for different cooling down periods. In order to estimate the total radioactivity of 1-MW power target circuit (TC), which is developing now at IPPE, the contribution of its main components are preliminarily analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…5,56 One comparison shows that the resulting radiotoxicity from an ADS is indeed higher than that from a comparable reactor due to the accumulation of spallation products, and it takes about 300 years for their radiotoxicity to decrease below that of natural uranium ore. 56 Another study compares the radiotoxicity of three different targets: lead, tungsten, and tin. 5 This study shows that initial radiotoxicities (primarily inhalation) of products generated from a lead target are higher than those from either a tungsten or tin target because of the accumulation of 90 Sr, 60 Co, 194 Hg, and 148 Gd.…”
Section: Radiotoxicity Of Spallation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,56 One comparison shows that the resulting radiotoxicity from an ADS is indeed higher than that from a comparable reactor due to the accumulation of spallation products, and it takes about 300 years for their radiotoxicity to decrease below that of natural uranium ore. 56 Another study compares the radiotoxicity of three different targets: lead, tungsten, and tin. 5 This study shows that initial radiotoxicities (primarily inhalation) of products generated from a lead target are higher than those from either a tungsten or tin target because of the accumulation of 90 Sr, 60 Co, 194 Hg, and 148 Gd.…”
Section: Radiotoxicity Of Spallation Productsmentioning
confidence: 99%
“…Previous studies involving heavy liquid-metal spallation targets have shown that important contributors to the radiotoxicity of an LBE-cooled target can yield higher radiotoxicities than fission products can. 56 Isotopes of concern for the LBE target (or any LBE-cooled target) include 208 CEM2k is the more recent physics module, which is why it yields slightly higher results for LBE (i.e., it produces additional isotopes) and is used in the remainder of the calculations for this research. Results using ICRP versus ICRP plus JAERI data are also compared in these two figures.…”
Section: Radiotoxicity Factorsmentioning
confidence: 99%